First records of xanthochromism in common snook, Centropomus undecimalis (Actinopterygii: Carangiformes: Centropomidae), collected in the Gulf of Mexico - Armando T. Wakida-Kusunoki; Vicente Anislado-Tolentino; Luis Fernando Del Moral-Flores; Rodolfo Castro-Barbosa (Acta Ichthyologica et Piscatoria)
The first case of xanthochromism in a female common snook, Centropomus undecimalis (Bloch, 1792), in the southern Gulf of Mexico is described. The specimen supporting this record was caught off the coast of Tabasco, Mexico and it represents the first fish case of this abnormal coloration in the Gulf of Mexico. The analyzed specimen measured 774 mm in total length. Its body was entirely orange with a lighter shade of orange on the belly, while the normal coloration of this fish species is dark to opaque grey with yellow to green tints on the dorsal part, silvery lateral side, white belly, and black lateral line. It is uncertain what caused this abnormality, but it is hypothesized that multiple environmental stressors, natural and anthropogenic, were responsible for the appearance of this particular abnormality and other similar cases in the area. Additional sampling and long-term monitoring are needed to determine the possible causes and their ecological impacts.